2020
DOI: 10.3389/fmicb.2020.607251
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity of Pinnacle and Conical Microbial Mats in the Perennially Ice-Covered Lake Untersee, East Antarctica

Abstract: Antarctic perennially ice-covered lakes provide a stable low-disturbance environment where complex microbially mediated structures can grow. Lake Untersee, an ultra-oligotrophic lake in East Antarctica, has the lake floor covered in benthic microbial mat communities, where laminated organo-sedimentary structures form with three distinct, sympatric morphologies: small, elongated cuspate pinnacles, large complex cones and flat mats. We examined the diversity of prokaryotes and eukaryotes in pinnacles, cones and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 85 publications
2
7
0
Order By: Relevance
“…This agrees with a previous study that has detected these phyla in the microbial mats from the McMurdo Ice Shelf (Varin et al, 2012). While similar 16S rRNA gene communities were identified for the microbial mats on the McMurdo Ice Shelf and Lake Untersee, we are also aware that PCR can lead to amplification biases (Greco et al, 2020;Jackson et al, 2021). Further evaluation of the composition will benefit from metagenomic approaches that cover all DNA, including ribosomal and protein-coding genes, without PCR.…”
Section: S and 18s Rrna Gene Diversity In The Meltwater Pondssupporting
confidence: 90%
“…This agrees with a previous study that has detected these phyla in the microbial mats from the McMurdo Ice Shelf (Varin et al, 2012). While similar 16S rRNA gene communities were identified for the microbial mats on the McMurdo Ice Shelf and Lake Untersee, we are also aware that PCR can lead to amplification biases (Greco et al, 2020;Jackson et al, 2021). Further evaluation of the composition will benefit from metagenomic approaches that cover all DNA, including ribosomal and protein-coding genes, without PCR.…”
Section: S and 18s Rrna Gene Diversity In The Meltwater Pondssupporting
confidence: 90%
“…Our study is the first detailed 18S rRNA gene highthroughput sequencing analysis of microbial mats on the McMurdo Ice Shelf. The 18S rRNA gene analysis suggested that microbial Eukaryotes had a lower richness than the Bacteria and Archaea, which was also found for microbial mats in the perennially ice-covered Lake Untersee and Lake Fryxell, Antarctica (Greco et al 2020), and been described from other ecosystems such as cryoconite holes in the McMurdo Dry Valleys (Sommers et al 2018). The communities were dominated by Ochrophyta, Chlorophyta and Ciliophora, and previous work on 18S rRNA gene clone library and morphological surveys had demonstrated that microalgae, especially diatoms, are present in meltwater ponds (Sutherland 2009;Jungblut et al 2012b).…”
Section: Distinct 16s and 18s Rrna Gene Microbial Communities Along Amentioning
confidence: 62%
“…The communities were dominated by Ochrophyta, Chlorophyta and Ciliophora, and previous work on 18S rRNA gene clone library and morphological surveys had demonstrated that microalgae, especially diatoms, are present in meltwater ponds (Sutherland 2009;Jungblut et al 2012b). Sommers et al (2018) and Greco et al (2020) also found abundance of ciliates and similar groups of ciliates in Lake Untersee and cryoconite holes from Taylor Valley glaciers; however, it appears that more ciliate 18S rRNA gene sequences were recovered from microbial mats on the McMurdo Ice shelf. In contrast, fungi had a lower relative abundance on the McMurdo Ice Shelf and cryoconite holes than in the microbial mats in the ice-covered Lake Untersee.…”
Section: Distinct 16s and 18s Rrna Gene Microbial Communities Along Amentioning
confidence: 83%
“…The total inorganic carbon (TIC) and total organic carbon (TOC) concentrations in the lake are very low (0.3-0.4 mg C L −1 ) 22 , 1-3 orders of magnitude lower than in the MDV lakes and Antarctic subglacial lakes [23][24][25][26] . Despite the ultra-oligotrophic, low-light conditions, and lack of a seasonal moat, the lake hosts a benthic microbial ecosystem composed of photosynthetic microbial mats, small cuspate pinnacles, and large conical stromatolitic structures to depths of at least 130 m [27][28][29][30] (Fig. 2).…”
mentioning
confidence: 99%
“…2). The top layer of the microbial mats comprises a carbonfixing cyanobacteria community (Tychonema sp., Phormidium sp., Leptolyngbya sp., and Pseudanabaena sp) that shift to a heterotrophic community in the underlying layers (Actinobacteria, Verrucomicrobia, Proteobacteria, and Bacteroidetes) 28,30,31 . The phototrophic mats are growing in very low light conditions: c. 5% of incident photosynthetically active radiation (PAR) irradiance is transmitted through the lake ice and decreases to c. 0.1% at a 135 m depth 27 .…”
mentioning
confidence: 99%